2018
DOI: 10.1016/j.jadohealth.2018.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Links Between Childhood Exposure to Violent Contexts and Risky Adolescent Health Behaviors

Abstract: Childhood exposure to violent contexts is associated with risky adolescent health behaviors, but the associations are context and behavior specific. After including covariates, we find no association between childhood exposure to violent contexts and obesity risk behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 31 publications
1
12
0
7
Order By: Relevance
“…13,14 Toxic stress-induced alterations also influence the adoption of maladaptive coping behaviors decades later. [37][38][39][40] Several researchers have noted that many other experiences in childhood are also associated with poor outcomes later in life, and these include being raised in poverty, 41 left homeless, [42][43][44] exposed to neighborhood violence, [45][46][47] subjected to racism, [48][49][50] bullied, 51,52 or punished harshly. 53 This wide spectrum of adversity underscores the fact that ACE scores and other epidemiologically derived risk factors at the population level are not valid or reliable predictors of outcomes at the individual level.…”
Section: Primary Preventions In the Frameworkmentioning
confidence: 99%
“…13,14 Toxic stress-induced alterations also influence the adoption of maladaptive coping behaviors decades later. [37][38][39][40] Several researchers have noted that many other experiences in childhood are also associated with poor outcomes later in life, and these include being raised in poverty, 41 left homeless, [42][43][44] exposed to neighborhood violence, [45][46][47] subjected to racism, [48][49][50] bullied, 51,52 or punished harshly. 53 This wide spectrum of adversity underscores the fact that ACE scores and other epidemiologically derived risk factors at the population level are not valid or reliable predictors of outcomes at the individual level.…”
Section: Primary Preventions In the Frameworkmentioning
confidence: 99%
“…Community violence has been defined as instances or threats of interpersonal harm within one's neighborhood or community (Kennedy & Ceballo, ), and has been associated with short‐term emotional and behavioral challenges, as well with long‐term mental health problems and financial instability (see Overstreet, for a review). Extensive research primarily from urban areas within the United States suggests that community violence has a particularly strong effect on adolescent externalizing behaviors, including aggression, delinquency, and substance use (James, Donnelly, Brooks‐Gunn, & McLanahan, ; Tache, Lambert, Ganiban, & Ialongo, ; Taylor et al., ; Taylor & Kliewer, ). In Colombia, Chaux, Arboleda, and Rincón () found that witnessing community violence and exposure to gangs was directly associated with higher adolescent aggressive behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…A research study conducted with Irish children and adolescents showed that adverse experiences in childhood and low income predict, independently, the risk of obesity at the beginning of adolescence 6 . In contrast, American researchers did not identify any association between exposure to violence in childhood and excess weight in adolescence 7 . There is still no consensus in the literature about the relationship between violence in childhood and increase in the Body Mass Index (BMI) among adolescents.…”
Section: Introductionmentioning
confidence: 85%
“…There is still no consensus in the literature about the relationship between violence in childhood and increase in the Body Mass Index (BMI) among adolescents. In addition to that, publications on the theme are mostly international [6][7] , the conduction of studies with Brazilian adolescents that may contribute to clarifying the theme thus becoming imperious. Therefore, this research aims to answer the following question: is there any association between violence in childhood and increase in the BMI during adolescence?…”
Section: Introductionmentioning
confidence: 99%